Mix and wait – a relaxed way for synthesizing ZIF-8. Issue 15 (22nd March 2022) - Gugin, Nikita; Villajos, Jose A.; Feldmann, Ines; Emmerling, Franziska
Abstract : Herein we report the synthesis of a zeolitic imidazolate framework (ZIF-8) by an easy "mix and wait" procedure. Abstract : Herein we report the synthesis of a zeolitic imidazolate framework (ZIF-8) by an easy "mix and wait" procedure. In a closed vial, without any interference, the mixture of 2-methylimidazole and basic zinc carbonate assembles into the crystalline product with approx. 90% conversion after 70 h. The reaction exhibits sigmoidal kinetics due to the self-generated water which accelerates the reaction.